The Rise Of Hizbut Tahrir In Indonesia: (A Global and Local Nexus) - Rijal, Syamsul (Fikroh: (Jurnal Studi Islam), 2023)
This article deals with the emergence and development of Hizbut Tahrir in Indonesia. It argues that its emergence and rapid development cannot be isolated from global and local socio-political context. The global element was related to Islamic resurgence in the late 1970s which inspired the flowering of Islamic movements in the Muslim world. The local element was related to the repressive state toward the articulation of political Islam that made Muslim students find Islam as the outlet in the midst of their frustration toward the state. During the Soeharto era, HTI went underground and focused its energy on dakwah and cadre building. After the demise of Soeharto, however, HTI found its momentum to emerge in Indonesian public and has utilized the new democratic political sphere to advance its cause.